Comparison of the FDA and ASCO/CAP Criteria for HER2 Immunohistochemistry in Upper Urinary Tract Urothelial Carcinoma - Gilhyang Kim; Yul Ri Chung; Bohyun Kim; Boram Song; Kyung Chul Moon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Background Human epidermal growth factor receptor 2 (HER2) is one of the known oncogenes in urothelial carcinoma. However, the association between HER2 and the prognosis of upper urinary tract urothelial carcinoma (UUTUC) has not yet been fully clarified. The aim of this study was to evaluate HER2 expression using the United States Food and Drug Administration (FDA) criteria and American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) criteria and compare their prognostic significance in UUTUC. Methods HER2 expression was evaluated in 144 cases of UUTUC by immunohistochemistry (IHC) using tissue microarrays. We separately analyzed HER2 expression using the FDA and ASCO/CAP criteria. The IHC results were categorized into low (0, 1+) and high (2+, 3+) groups. Results Using the FDA criteria, 94 cases were negative, 38 cases were 1+, nine cases were 2+, and three cases were 3+. Using the ASCO/CAP criteria, 94 cases were negative, 34 cases were 1+, 13 cases were 2+, and three cases were 3+. Four cases showing 2+ according to the ASCO/CAP criteria were reclassified as 1+ by the FDA criteria. High HER2 expression by both the FDA criteria and ASCO/CAP criteria was significantly associated with International Society of Urological Pathology high grade (p = .001 and p < .001). The high HER2 expression group classified with the FDA criteria showed significantly shorter cancer-specific survival (p = .004), but the HER2 high and low expression groups classified with the ASCO/CAP criteria did not show significant differences (p = .161) in cancer-specific survival. Conclusions HER2 high expression groups were significantly associated with shorter cancer-specific survival, and our study revealed that the FDA criteria are more suitable for determining HER2 expression in UUTUC.